The chromosome-level holly (Ilex latifolia) genome reveals key enzymes in triterpenoid saponin biosynthesis and fruit color change - Xu, Ke-Wang; Wei, Xue-Fen; Lin, Chen-Xue; Zhang, Min; Zhang, Qiang; Zhou, Peng; Fang, Yan-Ming; Xue, Jia-Yu; Duan, Yi-Fan (Frontiers in Plant Science, 2022)
The Ilex L. (hollies) genus of Aquifoliaceae shows high species diversity in tropical and subtropical regions of Asia and South America. Throughout the range of the genus, Ilex species have been widely used in beverage and medicine production and as ornamentals. Here, we assembled a high-quality, chromosome-level genome of Ilex latifolia, which has extremely high economic value because of its useful secondary metabolite production and the high ornamental value of its decorative red berries. The 99.8% genome sequence was anchored to 20 pseudochromosomes, with a total length of 766.02 Mb and a scaffold N50 of 33.45 Mb. Based on the comparative genomic analysis of 14 angiosperm species, we recovered I. latifolia as the sister group to all other campanulids. Two whole-genome duplication (WGD) events were identified in hollies: one shared ancient WGD in the ancestor of all eudicots and a recent and independent WGD in hollies. We performed a genome-wide search to screen candidate genes involved in the biosynthesis of pentacyclic triterpenoid saponins in I. latifolia. Three subfamilies of CYP450 (CYP71A, CYP72A, and CYP716A) appear to have expanded. The transcriptomic analysis of I. latifolia leaves at five developmental stages revealed that two CYP716A genes and one CYP72A gene probably play important roles in this biosynthetic pathway. In addition, we totally identified 12 genes in the biosynthesis pathways of pelargonidin and cyanidin and observed their differential expression in green and red fruit pericarps, suggesting an association between pelargonidin and cyanidin biosynthesis and fruit pericarp color change. The accumulation of pelargonidin and cyanidin is expected to play an important role in the ornamental value of I. latifolia. Altogether, this study elucidated the molecular basis of the medicinal and ornamental value of I. latifolia, providing a data basis and promising clues for further applications.